The Importance of Superplastizer Dosage in the Mix Design of Lightweight Aggregate Concrete Reinforced with Plypropylene Fiber - Shafigh P.; Yahaghi J. (EDP Sciences, 2023)
Aggregates; Compressive strength; Concrete mixtures; Concretes; Mechanical properties; Palm oil; Polypropylenes; Reinforced plastics; Reinforcement; Tensile strength; Compressive and splitting tensile strengths; Curing condition; Light weight aggregate; Light-weight aggregate concrete; Oil industries; Other properties; Splitting tensile strength; Superplasticizers; Light weight concrete